Syndromes and Disorders Associated with Omphalocele (II): OEIS Complex and Pentalogy Of Cantrell - Chih-Ping Chen (Elsevier, 2007)
Omphalocele-exstrophy-imperforate anus-spinal defects (OEIS) complex is characterized by a combination of omphalocele, exstrophy of the bladder, an imperforate anus, and spinal defects. Pentalogy of Cantrell is characterized by a combination of a midline supraumbilical abdominal wall defect, a defect of the lower sternum, a defect of the diaphragmatic pericardium, a deficiency of the anterior diaphragm, and congenital cardiac anomalies. This article provides a comprehensive review of OEIS complex and pentalogy of Cantrell, including the pathogenesis, prenatal diagnosis, differential diagnosis, and associated malformations. Omphalocele is an important sonographic marker for OEIS complex and pentalogy of Cantrell. Prenatal detection of an abdominal wall defect associated with multiple midline defects should alert one to the possibility of OEIS complex and pentalogy of Cantrell and prompt the genetic investigation and counseling of the disorders.